2023
DOI: 10.3847/1538-4357/acf217
|View full text |Cite
|
Sign up to set email alerts
|

The Cool Circumgalactic Medium of Low-redshift Star-forming Galaxies. I. Empirical Model and Mean Properties

Yakov Faerman,
Jessica K. Werk

Abstract: We present an analytic model for the cool, T ∼ 104 K, circumgalactic medium (CGM), describing the gas distribution, and thermal and ionization states. Our model assumes (total) pressure equilibrium with the ambient warm/hot CGM, photoionization by the metagalactic radiation, and allows for nonthermal pressure support, parameterized by the ratio of thermal pressures, η = P hot,th/P cool,th. We apply the model to the COS-Halos measurements and find that a nominal model with η … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 164 publications
0
4
0
Order By: Relevance
“…In the same vein, there may be updated parameterizations for the fraction of gas around dwarfs that is photoionized by the UV background and hence prevented from accreting (compared to our assumed values from It may be interesting to separately track the alreadycooled gas and explore various models for its evolution cold cloud scenarios; Maller & Bullock 2004;Faerman & Werk 2023). We also do not currently allow for the possibility that some fraction of cosmic accretion enters the CGM as filaments and directly deposits cold gas into the ISM without being subject to our normal energy flow cycle, which may be especially important at high redshift (e.g., Mandelker et al 2020) Pandya et al 2020;Gurvich et al 2023).…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…In the same vein, there may be updated parameterizations for the fraction of gas around dwarfs that is photoionized by the UV background and hence prevented from accreting (compared to our assumed values from It may be interesting to separately track the alreadycooled gas and explore various models for its evolution cold cloud scenarios; Maller & Bullock 2004;Faerman & Werk 2023). We also do not currently allow for the possibility that some fraction of cosmic accretion enters the CGM as filaments and directly deposits cold gas into the ISM without being subject to our normal energy flow cycle, which may be especially important at high redshift (e.g., Mandelker et al 2020) Pandya et al 2020;Gurvich et al 2023).…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…Assuming that cold clouds in the CGM are in local pressure equilibrium with the warm/hot phase, they reported that cold gas could be found out to 0.6 R vir or beyond. Although we examine more massive halos (10 13.5 M 200 10 14 M e ) compared to Faerman & Werk (2023), we also find that the CGM of Fornax-like halos normally shows a spatially extended distribution of cold gas clouds out to more than 0.5 R vir .…”
Section: Comparison To Other Cosmological Simulationsmentioning
confidence: 66%
“…Studying the spatial distribution and ionization state of cold gas in the CGM, Faerman & Werk (2023) performed semianalytical modeling of cold gas in the CGM of lowredshift star-forming galaxies. Assuming that cold clouds in the CGM are in local pressure equilibrium with the warm/hot phase, they reported that cold gas could be found out to 0.6 R vir or beyond.…”
Section: Comparison To Other Cosmological Simulationsmentioning
confidence: 99%
“…The measurements reported in this study are of H I and lowto-intermediate metal ions, and we assume they trace the cool, photoionized phase of the CGM at T ≈ 10 4 K (see also Faerman & Werk (2023) for a model of the cool CGM of L * galaxies). We set the gas spatial distribution in our model through two functions: (1) the hydrogen number density n H , and (2) the volume filling fraction, defined as the local volume fraction occupied by the cool gas clouds, f V ≡ dV cool /dV 1, where dV cool and dV = 4πr 2 dr are the cool gas and total volume of a shell at a given radius, respectively.…”
Section: Model Setupmentioning
confidence: 99%